PENERAPAN E-LEARNING EDMODO DITINJAU DARI HASIL BELAJAR MAHASISWA PGSD UNIVERSITAS SARJANAWIYATA TAMANSISWA - Trisniawati Trisniawati; Mahmudah Titi Muanifah; Martalia Ardiyaningrum (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to describe the effectiveness of e-learning edmodo in terms of learning outcomes of PGSD UST students, the effectiveness of group discussion learning in terms of student learning outcomes and comparing the effectiveness of e-learning edmodo and group discussion learning in terms of student learning outcomes. This type of research is a quantitative approach research that is quasi-experiment research. This research was conducted at the PGSD of UST. The subjects of this study were 2F and 2I semester students of PGSD UST. Data analysis method was carried out by one sample t-test and independent sample t-test. Data analyzed in the form of primary data, namely tests given to students. The results showed that mathematics learning using e-learning edmodo was more effective than mathematics learning using group discussion in terms of student learning outcomes. The lowest and highest learning outcomes obtained by the experimental class (e-leaning edmodo) were 36.05 and 88.15 with an average of 73.57. For the control group (group discussion) the lowest and highest learning outcomes were 38.50 and 92.40 with an average of 66.25.